The way to a man's heart is through his stomach - recommendations after a heart surgery (cardiac surgical) - Karolina Koszyczarek; Diana Marańska; Gabriela Różańska-Smuszkiewicz; Paweł Smuszkiewicz-Różański (Nicolaus Copernicus University in Toruń, 2024)
Introduction and Purpose: Understanding the crucial role of nutrition and sport in the postoperative recovery of cardiac surgery patients is paramount. Optimal nutrition aids in healing mitigates complications and enhances overall outcomes. This abstract focuses on the necessity of customized nutrition plans tailored to meet the unique recovery needs of post-cardiac procedures, emphasizing the importance of heart-healthy dietary choices for long-term cardiovascular health. Materials and methods: The literature available in PubMed, Scopus, and Google Scholar databases was reviewed using the following keywords: "nutrition"; "surgery nutrition; and "cardiac surgery nutrition" State of Knowledge: Evidence underscores the significance of a diet rich in omega-3 fatty acids, antioxidants, and soluble fiber in facilitating post-surgery recovery and promoting heart health. Strategies to reduce sodium and limit unhealthy fats are vital, as is incorporating whole grains, lean proteins, and various fruits and vegetables. Collaborative development of personalized dietary plans with healthcare professionals is critical for enhancing recovery and ensuring long-term health benefits. Conclusion: The integration of targeted nutritional strategies into postoperative care is essential for optimizing patient recovery and improving quality of life following cardiac surgery. Nutrition plays a foundational role in supporting the healing process, reducing the risk of complications and securing cardiovascular health in the long term.